Classification and use of landform information to increase the accuracy of land condition monitoring in Western Australian pastoral rangelands - Wilson, Deanna Marie (Curtin University, 2018)
The aim of this research was to develop land unit scale data to assist land condition monitoring projects in pastoral rangelands in Western Australia. Landforms are a major components of land units and methods were explored to include landforms as a variable in land unit predictive modelling. Three land unit prediction models were tested, a Binary Weighted Overlay (BWO), a Fuzzy Weighted Overlay (FWO) and a Positive Weights of Evidence (PWofE) model.